Prevalence and factors associated with anxiety and depression among Chinese prison officers during the prolonged COVID-19 pandemic - Zeng, Yuze; Xiao, Junze; Zhang, Qingqi; Liu, Xiaoqian; Ma, Ai (Frontiers in Public Health, 2023)
Objective This study examined the prevalence of anxiety and depression—along with the potential risk and protective factors—among Chinese prison officers during the prolonged COVID-19 pandemic. Method A cross-sectional survey of 1,268 officers from five prisons in western and southern China was administered between June and July 2022. The questionnaires comprised two sections. In the first section, the Generalized Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) were used to evaluate the prevalence of anxiety and depression, respectively, among prison officers. In the second section, the potential influencing factors were examined. Categorical data were compared using χ2 tests and t-tests; binary logistic regression analysis was performed to identify factors associated with anxiety and depression. Results The prevalence rates of anxiety and depression among the prison officers were 72.6% and 69.8%, respectively. Risk factors for anxiety were older age, being unmarried, work–family conflicts, job demands, and COVID-19 burnout; protective factors were exercise, positive family relationships, and group cohesion. Work–family conflicts, job demands, intolerance of uncertainty regarding COVID-19, and COVID-19 burnout were risk factors for depression, whereas annual income >150,000 RMB, exercise, positive family relationships, group cohesion, and job autonomy were protective factors against depression. Conclusion The prevalence of anxiety and depression among Chinese prison officers was relatively high during the prolonged COVID-19 pandemic, and more targeted measures should be implemented to improve their mental health. This study offers a reference for improving prison officers’ mental health in response to similar public health emergencies in the future.